2024
DOI: 10.1038/s41698-024-00501-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunological subtyping of salivary gland cancer identifies histological origin-specific tumor immune microenvironment

Jiyun Hong,
Eunwoo Choi,
Dahee Kim
et al.

Abstract: Gene expression analysis enhances proper cancer subtyping, a better understanding of the molecular characteristics of cancer, and strategies for precision medicine. However, salivary gland cancer (SGC) subtyping remains largely unexplored because of its rarity and diverse histopathological and immunological characteristics. This study aimed to determine whether the histological origin and immunological characteristics of SGC subtypes are intrinsic tumor immunity factors. We performed immune profiling of 94 RNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Immune checkpoint molecules, including PD-L1, programmed death ligand-2 (PD-L2), T-cell immunoreceptors with immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domains, and CTLA-4, are abundantly expressed in MECs with immune-hot TME compared to those with immune-cold TME [ 23 ]. Among SGCs, MECs show higher immune cell infiltration in the TME, greater T-cell receptor diversity, and increased expression of HLA class I and II than that of AdCCs [ 24 ]. Given that MEC may represent an immunogenetic tumor type where immunotherapies could be effective ( Figure 1 ), further research is necessary to examine the immunological differences in the TME across different histological grades of MEC.…”
Section: The Immunological Background Of Mucoepidermoid Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Immune checkpoint molecules, including PD-L1, programmed death ligand-2 (PD-L2), T-cell immunoreceptors with immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domains, and CTLA-4, are abundantly expressed in MECs with immune-hot TME compared to those with immune-cold TME [ 23 ]. Among SGCs, MECs show higher immune cell infiltration in the TME, greater T-cell receptor diversity, and increased expression of HLA class I and II than that of AdCCs [ 24 ]. Given that MEC may represent an immunogenetic tumor type where immunotherapies could be effective ( Figure 1 ), further research is necessary to examine the immunological differences in the TME across different histological grades of MEC.…”
Section: The Immunological Background Of Mucoepidermoid Carcinomamentioning
confidence: 99%
“…RNA-sequencing studies have revealed increased T-cell infiltration and neoantigen expression in SDCs compared to that of myoepithelial carcinoma or AdCC [ 30 ]. In addition to immune cell infiltration, another study has shown that SDCs express high levels of T-cell receptor diversity and HLA class I/II [ 24 ]. However, multiple immunosuppressive mechanisms co-exist in the TME of SDCs.…”
Section: The Immunological Background Of Salivary Duct Carcinomamentioning
confidence: 99%